Community participation as mediating variable for enhancement of citizen satisfaction in Malaysian municipal councils. Batu Pahat municipal council in perspective - Bello, Muhammad Umar; Daud @ Juanil, David Martin; Kasim, Rozilah; Aliyu, Aliyu Ahmad (JARDCS, 2018)
This study highlighted the important of community participation as mediating variable in municipal council service delivery and enhancing citizen satisfaction, it was also investigated the level of satisfaction of citizen in the study area. The important and effects of quality municipal service, municipal awareness, community participation was also highlighted. The study was conducted in Batu Pahat Municipal Council, so the item of measurement of the variables has been tested and confirmed their reliability and consistence of the survey instrument. Some hypothesis was postulated using the research variables. Vivid explanation of variables and their relationship. The study provides a structural model for enhancing citizen satisfaction. Questionnaires was developed and administered using simple random sampling. The respondents for this research was 401,921, the samples size was 383 but it was rounded to 400 respondents. The study employed some hypotheses in order to guide the research in achieving the overall aim of the research as well as testing the stated hypotheses and the diagrammatic representation was presented and also the factor analysis was conducted to measure the reliability of the research constructs, multivariate was conducted by using Spss IBM version 23 and Structural Equation Modelling (SEM). The findings of the study reveal that community participation, municipal awareness and quality municipal services are the major drivers of citizen satisfaction in study area. In addition, using community participation as mediating variable will enhance citizen satisfaction, the study also found a strong empirical evidence for enhancing citizen satisfaction. The study concluded that citizen satisfaction can be enhance through adding community participation as mediating factors, municipal awareness also should be inculcated to makes the local people enlighten about the process of municipal service delivery.